Thermal analysis, camphene hydroformylation and hydrogenation of limonene with triphenylphosphine complexes, ruthenium (II) containing n-heterocyclic ligands (Revista de Investigaciones Universidad del Quindío, 2010)
We report thermal studies of thermogravimetry (TGA) and catalytic activity in the hydroformylation in homogeneous phase of camphene using complexes [RuCl2 (PPh3)2(N-het)2], where the N-heterocyclic are: 2- acetylpyridine (2-acpy); 3- acetylpyridine (3-acpy), 4-acetylpyridine (4-acpy), 2-aminopyridine (2-Ampy) 3 aminopyridine (3-Ampy) and 4 - aminopyridine (4-Ampy). TGA studies showed that the complexes present mass loss which was assigned to the dissociation of ligands, most of the complexes dissociate a triphenylphosphine and a N-heterocyclic ligand in the first decomposition, to then undergo the total decomposition of the complex or the dissociation of another ligand. In the camphene hydroformylation the position of the substituents on the pyridine ring exerts a remarkable influence on selectivity and catalyst activity, the substituents donors of charge density in the pyridine ring and that are located in ortho-positions induce the complex to be less active than when the complex presents pyridinic substituents in para-position. The same phenomenon is observed with complexes where the pyridine ring is substituted by groups of attractors of charge density.
Keywords: hydroformylation; hydrogenation; ruthenium (II); terpenes